An Urban Scheme for the ECMWF Integrated Forecasting System: Single‐Column and Global Offline Application. (17th June 2021) - McNorton, J. R.; Arduini, G.; Bousserez, N.; Agustí‐Panareda, A.; Balsamo, G.; Boussetta, S.; Choulga, M.; Hadade, I.; Hogan, R. J.
Abstract: The societal benefits of numerical weather prediction (NWP) forecasts are most evident in populated areas. An urban representation within NWP models should provide improved forecast accuracy. Here, we present the preliminary implementation of an urban scheme within the Integrated Forecasting System (IFS) using a simplified single‐layer urban canopy model. The scheme makes assumptions of canyon geometry and considers fluxes from roads, walls, and roofs. Temperature observations were used to optimize single‐column model (SCM) parameters using the Gauss‐Newton method. Observation comparisons over six European cities, show a 2‐m temperature root‐mean‐squared error reduction from 1.85  to 1.75 K with the urban scheme. Optimized parameters were used globally at kilometric scale in a land surface model. A sensitivity experiment assuming a 100% urban world showed spatially averaged northern hemisphere 2‐m temperatures increased by 0.54 K (January) and 0.42 K (July) at night caused by changes in the albedo, emissivity, roughness, and thermal and hydrological properties. Global ∼1‐km resolution simulations using ancillary urban mapping information produce an urban heat island effect over major and minor conurbations. Only major conurbations were well represented at ∼9‐km resolution. Results from SCM simulations show a heightening of the planetary boundary layer over city sites, with the largest enhancements occurring at night in July (84 ± 48 m) caused by an increased sensible heat flux. These initial developments show the importance of a high‐resolution urban representation within NWP models. Improved parameterization and mapping will enable an online representation of energy, water, and trace gas fluxes over residential areas. Plain Language Summary: Urban areas make up only a small fraction of the Earth's surface; however, they are home to over 50% of the world's population. In these areas a phenomenon known as the urban heat island effect causes increased temperatures due to human activities, an effect often missing in weather forecasts. Forecasts, generated using computer models, consider not only the atmosphere but also the role of the land surface on the weather above. Typically these models do not include an urban map, so they miss key urban processes. We introduced a representation of urban areas to the model of the European Center for Medium‐Range Weather Forecasts. We considered several ways in which the urban environment interacts with the weather, including through changes in heat storage and treatment of rainfall. We find these developments result in a more accurate model forecast over six European cities. The model accurately predicts the increased heating observed over cities at night and some of the observed changes in the atmosphere. Future work should continue to improve the urban representation in weather and air quality/greenhouse gas models by implementing an urban scheme in operational forecasts. Key Points: An urban scheme has been introduced and optimized within the ECMWF IFS single‐column and surface‐only model Assuming an urban world, average nighttime 2‐m temperatures increased for January (0.54 K) and July (0.42 K) in a surface only simulation Using realistic urban cover for eight cities, PBL height in July increases by an average of 66 and 84 m for the day and night, respectively